COMPARISON OF ENVIRONMENTAL THOUGHTS OF DOMESTIC AND INTERNATIONAL STUDENTS LIVING IN NORTHERN CYPRUS - Kiraz, Aşkın; Salman, Subhi Ahmad Mahmoud (International Online Journal of Education and Teaching, 2021)
The aim of this study is to identify the environmental knowledge and the environmental awareness level of the university students. With this aim it is considered to compare the thoughts and the point of views between the international and domestic students’ environmental knowledge about North Cyprus. The case study has been used as a design of the study with qualitative research method. This study was conducted with 42 students from a university in northern Cyprus. The sample has been stated in two groups; the international students group that composed from 21 international students from different countries and the domestic students group that composed from 21 students from northern Cyprus. The research data were collected through interviews. Content analysis was used as a data analysis technique. Research findings show in general that the international students have less environmental awareness from the domestic students. In the light of the answers of the students and the results of the study, it has been suggested that the basic solution for creating a good environmental consciousness is environmental education.